Perilla Leaf Extract (PLE) Attenuates COPD Airway Inflammation via the TLR4/Syk/PKC/NF-κB Pathway In Vivo and In Vitro - Yuan, Jiqiao; Li, Xuyu; Fang, Nan; Li, Ping; Zhang, Ziqian; Lin, Mingbao; Hou, Qi (Frontiers in Pharmacology, 2022)
Chronic obstructive pulmonary disease (COPD) is a complex and heterogeneous disease characterized by persistent airflow limitation but still lacking effective treatments. Perilla frutescens (L.) Britt., an important traditional medicinal plant with excellent antioxidant and anti-inflammatory properties, is widely used for the treatment of respiratory disease in China. However, its protective activity and mechanism against COPD airway inflammation have not been fully studied. Here, the anti-inflammatory effects of the PLE were investigated, and its underlying mechanisms were then elucidated. The presented results suggested a notable effect of the PLE on airway inflammation of COPD, by significantly ameliorating inflammatory cell infiltration in lung tissue, lessening leukocytes (lymphocytes, neutrophils, and macrophages) and inflammatory mediators (interleukin 4 (IL-4), IL-6, IL-17A, interferon γ (IFN-γ), and tumor necrosis factor α (TNF-α)) in the bronchoalveolar lavage fluid (BALF) of cigarette smoke (CS)/lipopolysaccharide (LPS)-induced COPD mice in vivo and inhibiting the production of inflammatory factors (nitric oxide (NO), IL-6, and TNF-α) and intracellular reactive oxygen species (ROS) in LPS-stimulated RAW264.7 cells in vitro. For further extent, PLE treatment significantly suppressed the expression and phosphorylation of TLR4, Syk, PKC, and NF-κB p65 in vivo and their mRNA in vitro. Subsequently, by co-treating with their inhibitors in vitro, its potential mechanism via TLR4/Syk/PKC/NF-κB p65 signals was disclosed. In summary, the obtained results indicated a noteworthy effective activity of the PLE on COPD inflammation, and partly, the TLR4/Syk/PKC/NF-κB p65 axis might be the potential mechanism.